Evaluation of the profile of interventions performed by clinical pharmacist and multidisciplinary after the implementation of the FASTHUG methodology in an intensive care unit - Alex Junior SOUZA; Fernanda Weyand BANHUK; Andressa ALMEIDA; Simone Von GROLL; Andreia Cristina SANCHES; Luciane Fátima CALDEIRA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2023)
Objective: To evaluate the profile of pharmaceutical and multidisciplinary interventions after the implementation of the FASTHUG mnemonic in a multidisciplinary meeting of an adult intensive care unit and the presence of a clinical pharmacist in this team. Methods: Cross-sectional study, in which 225 patients were monitored, through the analysis of demographic and clinical data from electronic medical records provided by the clinical pharmacy service of the University Hospital of Western Paraná and evaluation of interventions carried out through monitoring indicators. Multidisciplinary and pharmaceutical interventions were recorded during multidisciplinary meetings and classified according to the mnemonic FASTHUG, which covers aspects such as nutrition, analgesia, sedation, thromboembolism prophylaxis, elevated headboard, stress ulcer prophylaxis and glycemic control. Results: 1078 interventions were carried out, with an average of 4.79 interventions per patient monitored. The most frequent multidisciplinary interventions were addition of necessary medication 248 (27.2%), diet optimization 145 (15.9%), analgesia optimization 128 (14%), glycemic control optimization 109 (12%), frequency of administration and suspension of unnecessary medication, both 68 (7.5%). The most common pharmaceutical interventions were optimization of administration frequency 40 (24.3%), addition of necessary medication 18 (11%), suspension of unnecessary medication 17 (10.3%) and change in dose reduction 15 (9.1%). Regarding patient outcomes, 75.1% were discharged to the ward, 24.4% died and 0.4% were transferred to another hospital. Conclusion: The implementation of the FASTHUG mnemonic in an intensive care unit provided a standardization of language among the multidisciplinary team during clinical meetings, as well as enabling the evaluation of essential points of pharmacotherapy by the clinical pharmacist.